ANALISIS EKSPLORATIF TERHADAP PEMIKIRAN YŪSUF AL-QARḌĀWĪ TENTANG KESETARAAN DAN KEADILAN GENDER SEBAGAI BAGIAN MAQᾹṢID AL-QUR’ᾹN - Yaqin, Ainol (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
Gender justice and gender equality are complex topics and drew the attention of many people. A number of Muslim jurists have studied it from various perspectives in order to understand and find a fair solution to the problem. However, most of them are rare to study it from the lens of maqÄá¹£id al-Qurâ€™Än, the purpose of al-Qurâ€™an was revealed to the earth. Incorporating gender justice and gender equality in maqÄá¹£id al-Qurâ€™Än is considered urgent with the intent that people will really pay attention, watch, and put male and female proportionally. This paper focuses on analyzing YÅ«suf al-Qará¸ÄwÄ«'s thought about gender equality and justice as part of maqÄá¹£id al-Qurâ€™Än. This article includes library research, whose datas are sourced from the literature. The results of this study revealed that men and women have equal rights in every aspect of life; education; economics, social, political, and law. They are also given equal rights in participating to be public leaders. Besides that, they have equal rights in selecting their belief (religion) based on their strong desire and their own belief and they have rights to get heritance as well as having rights to the goods they have. On the contrary, any kinds of discriminations, subordination, stereotyping, violence, and all forms of deviation inequality of gender bias, contradict and contrasted with maqÄá¹£id al-Qurâ€™Än.